Singlejet fluidized beds: experiments and CFD simulations with glass and polypropylene particles - Utikar, Ranjeet P.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
Understanding hydrodynamics of bubbling fluidized beds is crucial in proper design and scale up of these beds. CFD models have shown promise in gaining this understanding. In order to generate confidence in CFD models, predicted time averaged and dynamical characteristics of the bubbling fluidized beds need to be validated against experimental data. This paper describes such studies with rectangular fluidized beds operated with a central jet. Digital image analysis and analysis of wall pressure fluctuations were used for this characterization. Fluidization of two types of particles, glass and polypropylene (PP) was studied at two different initial bed heights of H/D = 1 and 2 with three central jet velocities 5, 10 and 20 m/s. Time averaged as well as dynamical characteristics were studied. The Eulerian-Eulerian two fluid model based on kinetic theory of granular flows was used to simulate these experiments. The predicted results were compared with the experimental data and previously published correlations. Although, there is agreement with experimental data in some aspects, complete agreement was not found. The presented experimental data and comparison with CFD predictions will provide useful basis for further work on understanding bubbling fluidized beds. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; fluidized beds; hydrodynamics; image analysis; pressure fluctuations; single jet